2018
DOI: 10.2118/185936-pa
|View full text |Cite
|
Sign up to set email alerts
|

Correlation-Based Adaptive Localization With Applications to Ensemble-Based 4D-Seismic History Matching

Abstract: Summary Ensemble-based history-matching methods have received much attention in reservoir engineering. In real applications, small ensembles are often used in reservoir simulations to reduce the computational costs. A small ensemble size may lead to ensemble collapse, a phenomenon in which the spread of the ensemble of history-matched reservoir models becomes artificially small. Ensemble collapse is not desired for an ensemble-based history-matching method because it not only deteriorates the ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 4 publications
0
52
0
Order By: Relevance
“…Localization is one of the most common regularization techniques used in ensemble-based historymatching applications (Oliver and Chen, 2011). In general, localization methods fall into two categories: distance-based (Chen and Oliver, 2010;Emerick and Reynolds, 2011) and non-distance-based (Zhang and Oliver, 2010;Luo et al, 2018) localization methods. In distance-based localization, one assumes that any covariance beyond a certain distance is purely a result of sampling errors.…”
Section: Kalman Gain Localizationmentioning
confidence: 99%
“…Localization is one of the most common regularization techniques used in ensemble-based historymatching applications (Oliver and Chen, 2011). In general, localization methods fall into two categories: distance-based (Chen and Oliver, 2010;Emerick and Reynolds, 2011) and non-distance-based (Zhang and Oliver, 2010;Luo et al, 2018) localization methods. In distance-based localization, one assumes that any covariance beyond a certain distance is purely a result of sampling errors.…”
Section: Kalman Gain Localizationmentioning
confidence: 99%
“…1 because they do not consider the geological meaning of reservoir parameters. It has been reported that this problem can be solved by techniques such as localization in many studies (Watanabe and Datta-Gupta 2012;Luo et al 2018;Jung et al 2018). Since this research is not a study to improve the ensemble-based method, only the standard ensemble-based methods are used as a comparison of the proposed method.…”
Section: Characterization Of Channel Connectivitymentioning
confidence: 99%
“…However, small ensembles can cause a series of problems, including rank deficiency, distanced spurious correlations, and Monte Carlo sampling errors [6][7][8][9]. Therefore, a number of auxiliary techniques have been developed and reported in the literature, including covariance inflation, as well as localization and hybrid covariances [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in certain circumstances, model variables or the corresponding observation may not have associated physical locations, which may violate the principles of distance-based methods. Therefore, some adaptive localization methods, which may not be based on physical distances, have been proposed [14,22,24]. For instance, De La Chevrotiere and Harlim [24] proposed a data-driven method for improving the poorly estimated sample correlation by using a linear map.…”
Section: Introductionmentioning
confidence: 99%